2020
DOI: 10.1111/tpj.14689
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of MYB30 enhances salt tolerance by elevating alternative respiration via transcriptionally upregulating AOX1a in Arabidopsis

Abstract: SummarySalt stress reduces crop growth and productivity globally. Here we report that a R2R3‐MYB transcription factor MYB30 participates in salt tolerance in Arabidopsis. MYB30 can be SUMOylated by SIZ1 in response to salt stress and the lysine (K)283 of MYB30 is essential for its SUMOylation. In contrast to wild‐type MYB30, the MYB30K283R mutant failed to rescue the salt‐sensitive phenotype of the myb30‐2 mutant, indicating that SUMOylation of MYB30 is required for the salt‐stress response. Through transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…The primers used for qRT‐PCR are listed in Supporting Information Table S1. Ubiquitin 10 was used as an internal control (Gong et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The primers used for qRT‐PCR are listed in Supporting Information Table S1. Ubiquitin 10 was used as an internal control (Gong et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In response to salt stress, MYB30 directly binds to the promoter of AOX1a to promote its expression, thus maintaining the cellular redox homeostasis through enhanced Alt respiration. Overexpression of AOX1a can rescue the myb30 salt-sensitive phenotype [ 63 ]. In addition to flavonoid biosynthesis and ROS scavenging, overexpression of MYB12 also upregulated the expression of genes involved in ABA and proline biosynthesis, thus conferring salt tolerance to the plants [ 22 , 25 ].…”
Section: Mybs Modulate Salt Tolerancementioning
confidence: 99%
“…Alternatively, as the MBSs and EIN3‐binding site (EBS) are adjacent to each other in RSL4 promoter region, it is possible that the association of EIN3 with EBS might decrease the accessibility of MYB30 to MBSs. Furthermore, numerous studies have demonstrated that MYB30 undergoes specific post‐translational modification(s) (PTMs) such as SUMOylation, S ‐nitrosylation and ubiquitination in response to various stimuli (Gong et al ., 2020; Marino et al ., 2013; Tavares et al ., 2014; Zheng et al ., 2018; Zheng et al ., 2012). These PTMs might in turn stabilize the MYB30‐EIN3 complex or change the MYB30 configuration directly, resulting in disassociation of MYB30 from RSL4 promoter, leading to enhanced RH growth.…”
Section: Disscussionmentioning
confidence: 99%
“…Interestingly, it has been reported that MYB30 links reactive oxygen species signaling, root cell elongation and plant immune response (Mabuchi et al ., 2018). Functional investigations have revealed that MYB30 is involved in abscisic acid and brassinosteroid signaling, photomorphogenic development as well as heat stress response and salt tolerance (Gong et al ., 2020; Li et al ., 2009; Liao et al ., 2017; Yan et al ., 2020; Zheng et al ., 2012). However, it is not clear whether MYB30 plays a regulatory role in plant RH development.…”
Section: Introductionmentioning
confidence: 99%